Pengaruh Program Mentoring terhadap Pembentukan Karakter Tunas Remaja - Rejoice Leny Simatupang; Yonatan Alex Arifianto (STT Bala Keselamatan Palu, 2022)
Abstract:Currently, pre-teens or juvenile shoots in facing their development both physically, emotionally, and spiritually should be guided, supported and also fostered so that they do not take wrong steps in passing the developmental stages of their lives. The mentoring program is an option that can be used as a means to minimize the character and actions of youth shoots that do not reflect the character of the Lord Jesus. This study aims to determine how much influence it has, and also to find out the results of the mentoring program in shaping character, so this research focuses on the implementation of the Christian Religious Education mentoring program held at the Voice of the Bible Church. With the intention that in the end this mentoring program is expected to form early adolescents with character. This study uses quantitative methods with research subjects consisting of mentors, mentors, and mentoring participants. The result of this program is that there is an influence of the mentoring program on juvenile shoots so that teenage buds get a change in character, namely discipline, honesty, independence, tolerance, responsibility, good morals, a sense of wanting to help, a sense of wanting to help, a sense of caring for others, a sense of caring for the environment, a sense of belonging. want to help, be polite, and also respect others through character building through a mentoring program at the Voice of the Truth Gospel Church in Artha Gading Mall Rehobot by 64.3%.Abstrak:Saat ini yang pra-remaja atau tunas remaja dalam menghadapi perkembangannya baik dari segi fisik, emosional, dan spiritual seharusnya dibimbing, didukung dan juga dibina agar tidak salah langkah dalam melewati tahap perkembangan kehidupannya. Program mentoring menjadi pilihan yang dapat dijadikan sebagai sarana dalam meminimalisir karakter dan tindakan-tindakan tunas remaja yang tidak mencerminkan karakter Tuhan Yesus. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruhnya, dan juga mengetahui hasil program mentoring dalam membentuk karakter, sehingga penelitian ini berfokus pada pelaksanaan program mentoring Pendidikan Agama Kristen yang diadakan di Gereja Suara Kebenaran Injil. Dengan maksud pada akhirnya program mentoring ini diharapkan dapat membentuk remaja awal yang berkarakter. Penelitian ini menggunakan metode kuantitatif dengan subjek penelitian terdiri atas pembina mentoring, mentor, dan peserta mentoring. Hasil dari program ini adalah ada pengaruh program mentoring terhadap tunas remaja sehingga tunas remaja mendapatkan perubahan karakter yaitu disiplin, jujur, mandiri, toleransi, bertanggung jawab, bermoral baik, rasa ingin menolong, rasa ingin membantu, rasa peduli sesama, rasa peduli lingkungan, rasa ingin menolong, sopan, dan juga menghargai orang lain lewat pembentukan karakter melalui program mentoring di Gereja Suara Kebenaran Injil Rehobot Mall Artha Gading sebesar 64,3 %.